2022
DOI: 10.1155/2022/4525873
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Action of Zhi Gan Cao Decoction for Atrial Fibrillation and Myocardial Fibrosis in a Mouse Model of Atrial Fibrillation: A Network Pharmacology-Based Study

Abstract: Atrial fibrillation (AF), a commonly seen cardiac disease without optimal curative treatment option, is usually treated by traditional Chinese medicine in China. The Zhi-Gan-Cao decoction (ZGCD) is an alternative medicine for clinical use and has definitive effects. It remains to be defined regarding the specific components and related mechanisms of ZGCD for the treatment of AF. We determined the primary constituents and major targets of the herbs in ZGCD using the TCMSP, HERB, and BATMAN-TCM databases. The Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Thus, it can be concluded that the incidence and duration of AF can be effectively reduced via repressing fibrosis (Boyle et al., 2021; Heijman et al., 2014). In our study, GA reduced myocardial fibrosis area in a concentration‐dependent manner, analogous to the previous report demonstrating the effects of licorice‐related bioactive substances and compounds on attenuating myocardial fibrosis (Gao, Kan, et al., 2022; Han et al., 2022). Moreover, GA has been documented to exert its anti‐inflammatory effects on AF and to effectively inhibit the expressions of inflammatory factors (IL‐4, IL‐6, IL‐13, and IL‐17).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it can be concluded that the incidence and duration of AF can be effectively reduced via repressing fibrosis (Boyle et al., 2021; Heijman et al., 2014). In our study, GA reduced myocardial fibrosis area in a concentration‐dependent manner, analogous to the previous report demonstrating the effects of licorice‐related bioactive substances and compounds on attenuating myocardial fibrosis (Gao, Kan, et al., 2022; Han et al., 2022). Moreover, GA has been documented to exert its anti‐inflammatory effects on AF and to effectively inhibit the expressions of inflammatory factors (IL‐4, IL‐6, IL‐13, and IL‐17).…”
Section: Discussionsupporting
confidence: 91%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%